Tourist Attraction, Service Facilities and Consumer Convenience on Tourist Satisfaction Visiting Belimbing Kuok Island Tourism Village, Kampar Regency. - Lisa Tinaria; Yayu Kusdiana (LPPM Institut Studi Islam Sunan Doe, 2022)
Kampar Regency is one of the regencies in Riau Province with an area of 11,289.28 km2. The purpose of this study was to determine the effect of tourist attraction, service facilities and consumer convenience on the satisfaction of tourists visiting the Pulau Belimbing Kuok Tourism Village, Kampar Regency. The population of this study were all Belimbing Kuok island tourists, with a sample of 100 people using the slovin formula with accidental sampling technique. This research is in quantitative form with multiple linear regression methods and uses the SPSS program. The results of the T test and F test show that each variable or simultaneously has an influence on the satisfaction of tourists visiting the Belimbing Kuok Island Tourism Village, Kampar Regency. The R Square test results are 53.9% while the remaining 46.1% is influenced by other variables that are not used in this study. This research still has limitations. in terms of small scope. For future researchers, the authors suggest conducting research by adding other variables used.